Comparative karyological analysis of four species of Aedes mosquitoes inhabiting the territory of the Republic of Kazakhstan - Alekseeva, S.; Andreeva , Yu.; Sibataeva , A.; Sibataev , A. (Fundamental and Experimental Biology, 2025)
Karyological analysis of 4 species of Aedes mosquitoes (Aedes vexans, Ae.caspius, Ae.cataphylla, Ae.subdiversus) collected on the territory of the Republic of Kazakhstan was carried out. As a result, the length of chromosomes of each species was measured, C- and DAPI staining and Fluorescent in situ hybridisation (FISH) of chromosomes with 18S rDNA sample were carried out. C- and DAPI staining showed localisation of heterochromatin in the centromere region. FISH revealed rDNA loci on chromosome 1 in Ae.cataphylla, and on chromosome 2 in Aedes vexans, Ae.caspius and Ae.subdiversus.